Pengaruh Nilai Tukar Rupiah, Tingkat Inflasi, Jumlah Nasabah, Dan Ukuran Perusahaan Terhadap Pendapatan Gadai Swasta - Sasli Rais; Wakhyudin Wakhyudin (CV ODIS, 2026)
The development of private pawnshops is increasing every year in Indonesia, with 200 private pawnshops expected to reach 200 by May 2026. However, their national revenue contribution is still small, at 3%. This study aims to determine the influence of the rupiah exchange rate, inflation rate, number of customers, and company size on the increase in private pawnshop revenue. In this case, the influence of the rupiah exchange rate (X1), inflation rate (X2), number of customers (X3), and company size (X4) on private pawnshop revenue (Y) was tested. The research method used a quantitative method, through an associative approach. The sampling method used purposive sampling. The data collection method used secondary data, in the form of annual time series data, 2017-2025. The data analysis method used multiple linear regression analysis. Referring to the findings of this study, it is concluded that the rupiah exchange rate partially has a positive and significant effect on private pawnshop revenue. The inflation rate does not have an effect and is not significant on private pawnshop revenue. The number of customers has a positive and significant effect on private pawnshop revenue. Company size has a positive and significant effect on private pawnshop revenue. Meanwhile, simultaneously, the rupiah exchange rate, inflation rate, number of customers, and company size have a positive and significant influence on increasing private pawn income.